Hubungan Stres Kerja dengan Kinerja Perawat di Ruang Rawat Inap RS Setukpa Bhayangkara Kota Sukabumi - Muhammad Syahda Abirama; Tara Indra Dirgantara, Rima Novianti Utami (Jurnal Pengabdian Ilmu Kesehatan, 2026)
The quality of bleeding care plays a crucial role in improving the quality of hospital services. Nurse performance is a key factor in the success of healthcare services, influenced by various aspects, one of which is work stress. This study aims to analyze the relationship between work stress and nurse performance. The method used was a quantitative cross-sectional design. The study sample consisted of 63 respondents selected using a total sampling technique. Data collection was conducted using the Expanded Nursing Stress Scale (ENSS) questionnaire to measure work stress levels, as well as a nurse performance questionnaire based on the instrument in Nursalam's book. Data analysis was performed using the Somers' D test to determine the strength and direction of the relationship between variables. The results showed a significant relationship between work stress and nurse performance, with a p-value of 0.046 (<0.05). The Somers' D coefficient of -0.23 indicates a weak, negative relationship, meaning that the higher the level of work stress experienced by nurses, the lower their performance tends to be. This finding underscores the importance of stress management in improving nurse performance and the quality of healthcare services in hospitals.